Two small knives by Edward Delaney - Crane, Katie (2020)
Two small knives made by Edward Delaney laying flat on a white table. The top knife has a worn wooden handle and a stubby, curved blade. The lower knife has a darker wood handle and a short straight back blade with a slight curved edge blade.